Optimal Diaphragmatic Breathing Patterns through Exercise Can Light Some Medical Problems - Asmaul Lutfi Marufah; Hilmy Yafi Zuhair; Ulfi Qomariyah Hanum; Agus Rubiyanto; Astri Dewayani; Abdurachman Latief (Jurnal Respirasi, 2022)
Breathing is an absolute human need. In an emergency, airway and breathing are the main problems that must be addressed immediately. Empirically, breathing techniques that people do in general are varied. Of all breathing patterns, it is believed that there must be the most optimal. One of them is diaphragmatic breathing (DB). DB plays the role of the diaphragm as the main muscle that performs the activity of inhaling and exhaling. Optimal breathing patterns, including certain DB, have the ability to relieve several medical problems. The aim of this study was to examine whether an optimal DB pattern could alleviate some medical problems. We conducted a literature study on 40 references consisting of 27 journals and 13 other appropriate literature sources. We searched library resources using the PubMed search engine through keywords: effectiveness of breathing, DB, and breathing exercises. Literature analysis was based on requirements, including inclusion and exclusion criteria. There were 26 journals which met the criteria. Optimal DB pattern can be a solution for chronic obstructive pulmonary disease (COPD), asthma, chronic stroke, congestive heart failure (CHF), gastroesophageal reflux disease (GERD), cerebral palsy (CP), labor pain management, and anxiety. It can be therapeutic to relieve some medical problems.